초음파 결합형 압통계를 활용한 압통시 소화불량 환자와 건강인의 복강내 조직 변화 비교: 비무작위 대조군 예비 임상시험 - 임진웅; 정태성; 정호석; 강선이; 최창민; 김동웅; Jinwoong Lim; Taeseong Jeong; Hoseok Jung; Sunny Kang; Chang-Min Choi; Dong Woung Kim (대한예방한의학회지, 2023)
Objectives : The aim of this study was to evaluate the differences in the abdominal cavity between functional dyspepsia patients and healthy people using an algometer combined with an ultrasound device. Methods : A non-randomized, controlled, pilot trial was conducted. Thirty patients in the experimental group and fifteen participants in the control group were recruited. We collected demographical data, and measured abdominal circumference, height of the body cavity, subcutaneous fat thickness, visual analogue scale of dyspepsia symptoms in the experimental group, depth of algometer and pressure of algometer when pressure pain occurred, and the whole ultrasonic image from the beginning of pressurization to the time when pressure pain occurred. The measurements were carried out twice with the duration of 1 week. Generalized linear regression was conducted to adjust baseline characteristics. Results : A total of 45 participants (30 in experimental group, 15 in control group) were recruited and finished the trial. Females were recruited more in the experimental group than in the control group and it was statistically significant. The difference in thickness of abdominal cavity between a second before the pressure pain and at the time when pressure pain occurred was statistically significant on 1st visit, and other measurements were not statistically significant. From the results of the regression analysis, the difference between two groups was statistically significant in the differences in the thickness of stomach and up to abdominal aorta on 1st visit, and the thickness of stomach on 2nd visit, and other measurements were not statistically different. Conclusions : According to the results, there were not statistically significant differences in abdominal examination when pressure pain occurred between dyspepsia patients and healthy people. Further studies are warranted to assess the abdominal examination using devices including algometer and ultrasound devices, regarding the results of the present study.